Trace gases CH4, N2O, and CO2 measured on discrete water samples during SONNE cruise SO283 - Bita Sabbaghzadeh; Stefan Otto; Gregor Rehder (PANGAEA, 2023)
The high surface productivity triggered by nutrient-rich Benguela upwelled waters results in significant enrichment of organic carbon in the sub-surface waters due to enhanced mineralization in the water column and benthic fluxes. Hence, microbial oxygen-consuming processes are promoted, driving oxygen depletion that favours trace gases i.e. methane (CH4) and nitrous oxide (N2O) production at relatively shallow depths. Also, gas-rich subsurface waters are transported towards the surface waters during upwelling, enhancing trace gas sea-air fluxes. Within the EVAR project, we investigate the variability of these fluxes on seasonal and shorter timescales to understand the intensity of the Benguela upwelling system as the source of these greenhouse gases relative to the atmosphere. The data might serve as a base for projections under a changing climate. The fieldwork took place during the cruise SO283 (March 19th – May 25th, 2021) onboard the R/V SONNE from and to Emden (Germany). The main area of the sampling was the Namibian shelf between 18°S and 25°S which is suggested to represent some regional hotspots of trace gas emissions to the atmosphere, in particular in the vicinity of the upwelling cells. Over 260 discrete water samples were collected from the Niskin bottles at different stations for the determination of the concentrations of CH4, N2O, and dissolved inorganic carbon (DIC). 200ml seawater samples were fixed with 200 μL of saturated HgCl2 solution straight after sampling and trace gas was quantified in return. Dissolved CH4 and N2O were measured by an in-house designed purge and trap system with a dynamic headspace method back on land. In brief, a subsample is purged with an inert ultrapure carrier gas of Helium, and the gases are focused on a cryo-trap operated at about -120°C. The volatile compounds are desorbed by rapid heating and analyzed by a gas chromatograph (GC; Agilent 7890B), equipped with capillary columns and a Deans Switch, which directed the components to the flamenionization detector for CH4 detection and electron capture detector ECD for N2O detection. To explore the carbonate system Dissolved Inorganic Carbon (DIC) was measured in the institute. About 5.00 ml of each fixed discrete sample was acidified by 10 % phosphoric acid, resulting in release of inorganic carbon content of the sample. An automated infra-red inorganic carbon analyzer (AIRICA, Marianda, Tulpenweg 28, D-24145 Kiel) equipped with an infrared detector LICOR 7000 (LI-COR Environmental – GmbH, Homburg, Germany) was used to quantify DIC. A 3-fold measurement of the pH was also carried out in 120 ml of discrete samples directly after sampling using the HydroFIA pH system (4H Jena Engineering, 24148 Kiel, Germany). We calculated the average pH value of the corresponding sample after Müller and Rehder (2018) and corresponding total alkalinity and pCO2 after Dickson et al. (2007).